Sociology of rural development - Nahar U.R.(ed.) Ambika Chandani(ed.) (Jaipur Rawat Publications, 1995)
Papers presented at a National Seminar on Rural Development organized in 1990 by Department of Sociology, Jai Narain Vyas University, Jodhpur to honor and felicitate late Prof. Sheo Kumar Lal, b. 1930.
Keywords: Rural development -- India